Vooraan vlnr.: Den Uyl, Van Agt; erachter: naast van Agt, Kooijmans, Van DAm, Lubbers, Van der Stee. Links achter Den Uyl: Rietkerk, ? , Andriessen (1973)
Vooraan vlnr.: Den Uyl, Van Agt; erachter: naast van Agt, Kooijmans, Van DAm, Lubbers, Van der Stee. Links achter Den Uyl: Rietkerk, ? , Andriessen.